Soccer and relative age effect: A walk among elite players and young players - Sierra-Diaz, M. J.; Gonzalez-Villora, S.; Pastor-Vicedo, J. C.; Serra-Olivares, J. (Sports, 2017)
Grouping people according to chronological age is popular in fields such as education and sport. Athletes who are born in the first months of the year usually have cognitive and physical development differences in contrast to those born in the last months of the same year. That is why competitive teams tend to select older players more often than youngsters. Age differences between athletes born in the same year as well as an over-representation of older players are known as the Relative Age Effect. This effect is extensively described in young and elite team sports such as basketball, volleyball or, ice-hockey, as well as in soccer. The purpose of this study is to examine the state-of-the-art of the Relative Age Effect in youth and elite soccer players. This review summarizes recent research articles on the Relative Age Effect related to competitive soccer from 2010 to 2016. The systematic literature search was conducted in four databases: SPORTDiscus, Medline, EBSCO host and Google Scholar. Although causes and final solutions have not been clearly achieved yet, it is necessary to continue investigating this phenomenon in order to provide a starting point for future research.